Lineage-Specific Early Differentiation of Human Embryonic Stem Cells Requires a G2 Cell Cycle Pause. (28th March 2016) - Van Oudenhove, Jennifer J.; Grandy, Rodrigo A.; Ghule, Prachi N.; del Rio, Roxana; Lian, Jane B.; Stein, Janet L.; Zaidi, Sayyed K.; Stein, Gary S.
Abstract: Human embryonic stem cells (hESCs) have an abbreviated G1 phase of the cell cycle that allows rapid proliferation and maintenance of pluripotency. Lengthening of G1 corresponds to loss of pluripotency during differentiation. However, precise mechanisms that link alterations in the cell cycle and early differentiation remain to be defined. We investigated initial stages of mesendodermal lineage commitment in hESCs, and observed a cell cycle pause. Transcriptome profiling identified several genes with known roles in regulation of the G2/M transition that were differentially expressed early during lineage commitment. WEE1 kinase, which blocks entry into mitosis by phosphorylating CDK1 at Y15, was the most highly expressed of these genes. Inhibition of CDK1 phosphorylation by a specific inhibitor of WEE1 restored cell cycle progression by preventing the G2 pause. Directed differentiation of hESCs revealed that cells paused during commitment to the endo- and mesodermal, but not ectodermal, lineages. Functionally, WEE1 inhibition during meso- and endodermal differentiation selectively decreased expression of definitive endodermal markers SOX17 and FOXA2. Our findings identify a novel G2 cell cycle pause that is required for endodermal differentiation and provide important new mechanistic insights into early events of lineage commitment. Abstract : Early after induction of differentiation to certain lineages there is an increase in nuclear WEE1 that phosphorylates the CDK1/cyclin complex at Y15, inhibiting progression into mitosis and forcing cells to pause in G2. This pause is seen in mesendoderm, mesoderm, and endoderm differentiation but is only required for endoderm differentiation.